Acetylcholinesterase and butyrylcholinesterase activities in cerebrospinal fluid from different levels of the neuraxis of patients with dementia of the Alzheimer type. - Appleyard, M E (1992)
Acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) activities of cerebrospinal fluid (CSF) collected post mortem from the lateral ventricles, cisterna magna, and lumbar regions of the spinal cord of patients with a histologically confirmed diagnosis of Alzheimer's disease were compared with those of normal, age matched control patients, patients with dementia of non-Alzheimer aetiology, and patients with non-dementing neurological disorders. The AChE activity of the ventricular CSF of patients with Alzheimer's disease was 48% lower (p < 0.005) than that of age matched controls or patients with other types of dementia, and the AChE activity of CSF sampled from the basal cistern was 40% lower (p < 0.005) in patients with Alzheimer's disease. There were no significant differences between the AChE activity in Alzheimer's disease and control patients in CSF collected from the lumbar cistern. AChE activity was lower in CSF sampled from the basal and lumbar cistern of patients with dementia of non-Alzheimer aetiology, while ventricular activity was in the normal range. BuChE activity in ventricular CSF of Alzheimer's disease patients was 41% lower than normal (p < 0.05) and in the normal range in all other samples. The secretion of AChE from forebrain and hindbrain regions is reduced in Alzheimer's disease patients, leading to decreased ventricular and cisternal levels of the enzyme. Secretion from more caudal regions of the central nervous system seems to be unaffected by the disease, resulting in AChE in the lumbar CSF of patients with Alzheimer's disease being in the control range. Such altered secretion of AChE in the brain could have profound implications not only for cholinergic transmission in these patients but also for the proposed noncholinergic modulatory actions of AChE.